I'm hoping someone can help me. I haven't done math in 11 years and am jumping back in the pool.

I am working on function notation and have figured most of it out....(i think)...but am confused on a few things.

This is the question i have been working on:

If ƒ(x) = 2x + 1, and g(x) = 3 - x, find:

a) f(a)

b) f(3a)

c) ƒ(x + 1)

d) g(y)

e) g(2x-3)

f) 2ƒ(x)

g) -2g(a)

Now I'm fairly sure I have figured out a-e for example for answer a my work was as follows:

f(a)=2a+1

g(2a+1)=3-(2a+1)

g(2a+1)=3-2a-1

g( f (a)) =2-2a

But I'm lost with f & g????? How do I work with the 2f(x) & the -2g(a)????????